SYSTOLIC STRAIN RATE IN LEFT VENTRICULAR DYSFUNCTION CAUSED BY RHEUMATIC CHRONIC SEVERE MITRAL REGURGITATION - Iqbal, Muhammad Khaleel; Maqbool, Muhammad Furrakh; Tawwab, Shahzad; Awan, Muhammad Saleem; Naveed, Tahir; Butt, Usman Mahmood (Journal of Ayub Medical College Abbottabad, 2020)
Background: In rheumatic severe mitral regurgitation, earlier detection of left ventricular dysfunction is very necessary in order to refer the patients for surgery at appropriate time. This study tried to find a correlation between conventional parameters of left ventricular dysfunction with systolic strain rate. Methods: A descriptive correlational study conducted from September 2016 to March 2018. One hundred and ninety-two patients of severe rheumatic MR and fifty-eight healthy controls were included. Left ventricular ejection fraction (LVEF), end diastolic dimension (LVEDD) and end systolic dimension (LVESD) were measured. Healthy controls were taken as group-I and patients were divided into group-II (ejection fraction ‰¥60% and LVESD ‰¤40 mm), group-III (ejection fraction ‰¥60% and LVESD ‰¤41-50 mm), and group-IV (ejection fraction <60%). Systolic strain rate at medial wall (SSR-med), at lateral wall (SSR-lat) and average of both (SSR-avg) were also measured by tissue doppler method for each study subject. Results: Out of 250 study subjects, males were 113 (45.2%) and females were 137 (54.8%). Means of the age, LVEF, LVEDD and LVESD were 30.8±9.1, 60.0±8.3, 58.5±7.8 and 37.4±9.9 respectively. Group I, II, III and IV contained 58, 69, 67 and 56 subjects respectively. Comparing these groups, mean LVEF progressively decreased from 63.9%±2.2 in group-I to 46.2±6.5 in group-IV while means of LVEDD and LVESD progressively increased from 45.9±3.5 and 23.2±2.3 in group-I to 64.3±3.6 and 49.0±2.9 in group-IV respectively. Average systolic strain rate (SSR-avg) decreased progressively from 1.57±0.06 in group-I to 0.83±0.08 in group-IV. All the strain rates, i.e., SSR-med, SSR-lat and SSR-avg showed significant negative correlation with left ventricular dysfunction, i.e., the group number (p<0.001). Conclusion: Systolic strain rate measured by tissue doppler method have significant negative correlation with left ventricular dysfunction in patients having rheumatic chronic severe mitral regurgitation. Keywords: Left ventricular dysfunction; Strain rate; Mitral regurgitation